Correlation of rabbit antithymocyte globulin serum levels and clinical outcomes in children who received hematopoietic stem cell transplantation from an alternative donor. (30th October 2015) - Elmahdi, Shaimaa; Muramatsu, Hideki; Narita, Atsushi; Torii, Yuka; Ismael, Olfat; Kawashima, Nozomu; Okuno, Yusuke; Sekiya, Yuko; Xu, Yinyan; Wang, Xinan; Hama, Asahito; Ito, Yoshinori; et al.
Abstract: We analyzed the correlation between rabbit ATG (rATG) serum levels and clinical outcomes in 37 children who received rATG at a total dose of 10 or 15 mg/kg during HSCT conditioning from an alternative donor. Fourteen patients had advanced malignant diseases, 13 had severe AA, and 10 had inherited disorders. Complete engraftment was achieved in all patients, and no rejection occurred. The cumulative incidence of grades II–IV acute GVHD and extensive chronic GVHD was 27% (95% CI, 12.5–39.6%) and 8.1% (95% CI, 0–23.1%), respectively. Multivariate analysis identified lower rATG levels at week 4 as an independent risk factor in the development of grades II–IV acute GVHD (p = 0.037). Serious infections were not observed in any patient following HSCT. No correlation was found between EBV reactivation and rATG levels at week 2 and week 4 after HSCT. Furthermore, no correlation was found between relapse and rATG levels two and four wk post‐transplantation. The probability of five‐yr OS among patients was 70.3% (95% CI, 59.8–79.2%). Our results suggest that targeted rATG administration may protect patients from severe acute GVHD without increasing the risk of EBV reactivation or relapse.